A influência neoliberal no processo de aprovação da Emenda Constitucional nº 95 e o financiamento da educação brasileira - Cella, Rosenei (2019)
This thesis has as object of study the Constitutional Amendment (Emenda Constitucional, EC) No. 95, of 2016, popularly known as the PEC do Teto, which instituted the New Tax Regime for the containment of public expenditures from the period of 2017. The question was: to what extent were the arguments used during the discussions that preceded the approval of Constitutional Amendment nº 95, in the Federal Legislature, which established limits for spending on public financing of education, were sustained by the neoliberal ideology? The EC nº 95 defines individual and global limits of public expenditures of the Union, and for the area of education it was established a level based on the minimum constitutional applied in the year of 2017, fixed amount from which year by year will be applied the readjustment by the IPCA (National Wide Consumer Price Index) for 20 consecutive years. The mechanism of operation of this planning signaled a growing reduction in the Union's investments in the area of education, which tends to promote a regression in the advances that had been observed in recent years in terms of policies that aimed the access and continuity at all educational levels, especially in higher education. To respond to the objective of the research, a bibliographic and documentary research was carried out, with the use of tachygraphic notes, which constitute the empirical material of this thesis. In addressing the financing of education, contributions from a group of authors who research public resources for education and educational policies, including Nelson Cardoso do Amaral, Luiz Fernandes Dourado and Nicholas Davies. As a theoretical contribution, regarding the neoliberalism, the writings of Friedrich Hayek and Milton Friedmann were mainly used, whose convictions support the neoliberal ideology. The debate that took place in the legislative arena was between two poles: on the one hand, the argument that education needs increasing investment and, on the other, that it is already spending too much. It is argued that investments increased without a commensurate improvement in the quality of education, that is, the speeches of the efficiency of public spending and fiscal austerity in line with the proposal under discussion. The constitutional binding of resources was another subject discussed in the legislative arena, because the economists understand that such mechanisms constrain the public budget and make it difficult for the government to plan efficient investments. However, historical data show that without the constitutional binding of resources for education, the area suffered significant declines in investments. The analysis of the empirical material exposed a number of important elements related to neoliberal ideology, because of this, we can affirm that the EC nº 95 is in harmony with neoliberal principles, and the main elements that prove this understanding is the defence of the size and responsibilities of the state, the argument for fiscal austerity and the efficiency of public spending as a substitute for expanding investment in public educational policies.